Procesos Morfológicos castellanos en el sustrato Culle y Castellano Andino de La Libertad - Blas García, Meregildo Samuel (2019)
ABSTRACT The thesis called Castilian morphological processes in the Culle substrate and Andean Castilian of La Libertad is a descriptive research of morphological aspects that presents the culle substrate in relation to the Castilian of the Andean area referred geographically to six provinces: Bolivar, Pataz, Sánchez Carrión, Santiago de Chuco, Julcán and Otuzco. The corpus seeks to respond to the concise need to explain the most important behaviors of the word formators in a comprehensive panorama, but at the same time responds to specific issues. Thus, they are the result of five years of research into spontaneous conversations and semi-directed interviews with the speakers with whom I interacted and worked. Basically I focused on rural areas such as hamlets, population centers and districts. The missing or poorly understood data were subjected to a new reformulation based on more data. Speakers from ten to one hundred years of age, men and women of different occupations and degrees of instruction participated. La Libertad region offers linguistic material rich in Culle data formations, influenced by the variety of Andean Castilian and vice versa. We register verbal paradigms that undergo reductions or variations of form in the conjugations; the flexivos show particularities of execution; the derivations change the grammatical categories; the diminutives and the augmentatives, as well as the lexical pieces coming from the original language and the foreign language are involved in similar behaviors. However, in exceptional situations of translation of a culle result, the equivalence to the Andean Castilian is limited and needs constructions or syntactic groups for its explicitation. This study of morphological description shows the regional linguistic reality of the liberteño Ande and orientates to other levels of analysis and other perspectives of interdisciplinary treatments for the dissemination of language behaviors and thus improve the relationships among human groups, the understanding and assessment of their linguistic systems in a particular contact situation.